Heat transfer in square duct fitted diagonally with angle-finned tape-Part 1: Experimental study - Promvonge, Pongjet; Skullong, Sompol; Kwankaomeng, Sutapat; Thiangpong, Chinaruk (My University, 2012)
The paper presents an experimental study on turbulent flow and heat transfer characteristics in a square duct fitted diagonally with 30° angle-finned tapes. The tested duct has a square section and uniform heat-fluxed walls and the flow rate of air used as the test fluid is presented in terms of Reynolds number from 4000 to 23,000. The angle-finned straight tape in the present work is newly invented without previous investigations available. The insertion of the finned tape is performed with three ratios of fin pitch to duct height (PR= P/. H) at the fin attack angle of 30° with respect to the main flow direction. The finned tape inserted diagonally in the duct is expected to generate a longitudinal vortex flow pair through the heated duct. Influences of five fin-to-duct height ratios (BR= b/. H= 0.1-0.3) for each fin pitch on thermal and flow friction characteristics of the inserted duct are investigated. The experimental result shows that at smaller fin pitch spacing, the finned tape with BR= 0.3 provides the highest heat transfer and friction factor but the one with BR= 0.2 and PR= 1.0 yields the best thermal performance. The thermal performance of the newly invented finned tape turbulator is found to be much higher than that of the wire coil/twisted tape turbulator. © 2012 Elsevier Ltd.
Keywords: Angle-finned tape; Friction; Heat transfer; Inserted duct; Square duct